مبادئ ونظريات التوجيه والارشاد.-1- - زموري, حميدة (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2024)
ملخص المطبوعة: تُعتبر وحدة "مبادئ ونظريات الإرشاد والتوجيه _1_" من الوحدات الأساسية المُهِمة التي لها أثرٌ كبيرٌ على تكوين الطالب في التربية وعلم النفس،وفي ضوء هذه الأهمية، تم إدراج هذه الوحدة ضمن خطط البرامج الدراسية تخصص "الإرشاد والتوجيه"، حيث يُتَوقعُ في نهاية تدريس هذه الوحدة أن يتكون طالب السنة الثالثة "توجيه وإرشاد"، تكويناً نظرياًّ من خلال اكتساب المفاهيم وإدراك أهمية الإرشاد في تحقيق النمو المُتكامل للفرد والتكيف الدراسي والعلمي والنفسي والاجتماعي، وتكويناً ميدانياًّ من خلال اكتساب المهارات والفنيات وأساليب الإرشاد الخاصة بكل نظرية، والتي سيتبناها خلال تعامله مع الحالات الإرشادية المُختلفة. كما ان لهذه النظريات أهمية كبيرة في توجيه عمل المرشد في مُساعدته في تحديد مشكلة العميل وطريقة التعامل معها". ومن خلال هذه المطبوعة سنحاول تحقيق أهداف هذه الوحدة الأساسية، حيث تم توزيع محتواها على ثلاث عشرة محاضرة مقسمة ضمن محورين: 01. المحور الأول: والمُعنون بــ "مبادئ الارشاد النفسي"، وسنتناول فيه تعريف التوجيه والإرشاد، نشأتُهُ ومراحل تطوره، علاقته مع العلوم الأخرى، وأهم مبادئه، ومجالاته. 02. المحور الثاني: المُعنون بـــ "نظريات التوجيه والإرشاد وتطبيقاتها"، وسنتناول فيه أهم نظريات الإرشاد وتطبيقاتها فيه، ومنها النظرية الإنسانية، النظريات السلوكية، المعرفية، الاتجاه الوجودي، الاتجاه الواقعي والاتجاه التكاملي. ويهدف تدريس وحدة "مبادئ ونظريات الإرشاد والتوجيه _1_" في تخصص السنة الثالثة "توجيه وإرشاد" إلى تحقيق الأهداف التعليمية الآتية: 01- أن يسترجع الطالب المُكتسبات القبلية حول التوجيه والإرشاد. 02- أن يُوسِّع الطالب مَدارِكه حول المجالات المُتعددة للتوجيه والإرشاد. 03- تمكينُ الطالب من توظيف المفاهيم النظرية في الإرشاد. 04- أن يتعرف الطالب على أهم النظريات وتطبيقاتها في الإرشاد. ولقد حاولنا من خلال هذه المطبوعة التطرق لمجموعة من أهم النظريات وأكثرها استخداماً في الإرشاد، كما دعمنا في بعض الأحيان المُحاضرات بأشكالٍ توضيحية تُساعد في فهم وتلخيص المحتوى المعرفي المُقترح وإنهائها بنماذج لأنشطةٍ تقويمية يُنجِزها الطلبة في نهاية كل محاضرة. The unit of “Principles and Theories of Counseling and Guidance _1_” is considered one of the important basic units that have a significant impact on the student’s acquisition in education and psychology. In light of this importance, this unit has been included in the plans of the study programs specializing in “Guidance and Counseling”.At the end of teaching this unit, it is expected that the third-year student will complete “Guidance and Counseling,” At the end of teaching this unit, it is expected that the third-year student will complete “Guidance and Counseling,” a theoretical training through acquiring concepts and realizing the importance of guidance in achieving the integrated growth of the individual and academic, scientific, psychological, and social adaptation, and a field training through acquiring the skills, techniques, and counseling methods specific to each theory. Which he will adopt during his dealings with various indicative cases. 01. The first axis: entitled “Principles of Psychological Counseling”, in which we will discuss the definition of guidance and counseling, its origins and stages of development, its relationship with other sciences, its most important principles, and its fields. 02. The second axis: entitled “Theories of Guidance and Counseling and Their Applications”, in which we will discuss the most important theories of guidance and their applications therein, including the humanistic theory, behavioral theories, cognitive theories, the existential trend, the realistic trend and the integrative trend. Teaching the unit “Principles and Theories of Guidance and Counseling _1_” in the third year specialization “Guidance and Counseling” aims to achieve the following educational objectives: 01- For the student to recall prior learning’s about guidance and counseling. 02- For the student to expand his awareness of the various fields of guidance and counseling. 03- Enabling the student to employ theoretical concepts in counseling. 04- For the student to become familiar with the most important theories and their applications in counseling. Through this publication, we have tried to address a group of the most important and most widely used theories in counseling. We have also sometimes supported the lectures with illustrative forms that help in understanding and summarizing the proposed cognitive content and ended them with models of evaluative activities that students complete at the end of each lecture
Keywords: التوجيه والإرشاد ،نظريات التوجيه والإرشاد، مبادئ التوجيه والارشاد، السنة الثالثة ليسانس.guidance and counseling, theories of guidance and counseling, principles of guidance and counseling, third year of bachelor’s degree